DEVELOPMENT PROSPECTS OF GASTRONOMIC TOURISM IN THE REPUBLIC OF UZBEKISTAN - Yusupov , Ne’matillo Saidturaevich; Sharobiddinov , Ahrorbek Qosimjon ugli (Innovative Development in Educational Activities, 2024)
Gastronomic tourism, or culinary tourism: is one of the main types of tourism, the main goal of which is to familiarize tourists with the national cuisine and food culture of that country during their trip to a certain country.